South African farm wages and working conditions: with special reference to the Albany district, 1957 to 1977 - Antrobus, Geoffrey Gordon (Rhodes University, Faculty of Commerce, Department of Economics, 1984)
The focus of the study is the wages and working conditions of farm labourers in commercial agriculture. After an outline examination of the broad trends in employment and wages in the agricultural industry as a whole, the emphasis falls on a micro-study of employment practices in the Eastern Cape magisterial district of Albany. The results of a survey of farmers was used to determine the level of wages, including payments in kind, the value of housing, cropping and grazing rights. It was found that cash wages made up only 25% of the total remuneration of R684 per annum, while purchased and farm produced rations made up a further 40% of the total. A survey conducted in the Albany district two decades previously was used to compare the real earnings in 1957 and 1977. Although real cash wages and rations increased over the twenty year period the restriction of cropping and grazing rights had the effect of keeping real earnings static. In the light of the improvement of other working conditions, such as the reduction in working hours, however, it is concluded that some increase in real wages did occur . It is evident that there are no clear-cut recipes for successful farm labour management and no unequivocal statements should be made about the most visible element, namely cash wages.
Keywords: Agricultural wages -- South Africa -- Eastern Cape; Agricultural laborers -- South Africa -- Eastern Cape